2020
DOI: 10.1093/treephys/tpaa092
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced root exudation of mature broadleaf and conifer trees in a Mediterranean forest during the dry season

Abstract: Root exudates are part of the rhizodeposition process, which is the major source of soil organic carbon (C) released by plant roots. This flux of C is believed to have profound effects on C and nutrient cycling in ecosystems. The quantity of root exudates depends on the plant species, the period throughout the year, and external biotic and abiotic factors. Since root exudates of mature trees are difficult to collect in field conditions, very little is known about their flux, especially in water-limited ecosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 44 publications
4
21
1
Order By: Relevance
“…We hypothesized that if re-fixation of respired CO 2 by the enzyme PEPC is the process that lowers tree-stems ARQ, organic acids that are the enzyme's products might be exported via the phloem to the roots and be secreted to the soil as root exudates (Hoffland et al, 1992;Shane et al, 2004). In agreement, a recent study in a different Mediterranean forest in Israel reported that root exudation rates were highest in the dry season and were associated with high soil temperature and low soil moisture (Jakoby et al, 2020). However, we found only weak and marginal inverse relation between ARQ ts and ARQ sa , which was expected if the organic acids are quickly decompose in the soil (Figure 7).…”
Section: Tree Stems Arq Shows Evidence For Seasonal Variable Re-fixationmentioning
confidence: 81%
“…We hypothesized that if re-fixation of respired CO 2 by the enzyme PEPC is the process that lowers tree-stems ARQ, organic acids that are the enzyme's products might be exported via the phloem to the roots and be secreted to the soil as root exudates (Hoffland et al, 1992;Shane et al, 2004). In agreement, a recent study in a different Mediterranean forest in Israel reported that root exudation rates were highest in the dry season and were associated with high soil temperature and low soil moisture (Jakoby et al, 2020). However, we found only weak and marginal inverse relation between ARQ ts and ARQ sa , which was expected if the organic acids are quickly decompose in the soil (Figure 7).…”
Section: Tree Stems Arq Shows Evidence For Seasonal Variable Re-fixationmentioning
confidence: 81%
“…We speculated that if re-fixation of respired CO 2 by the enzyme PEPC is the process that lowers tree-stems ARQ, the enzyme's products like the organic acids Confidential manuscript submitted to JGR Biogeosciences citrate and malate might be exported via the phloem to the roots and be secreted to the soil as root exudates [Hoffland et al, 2006;Shane et al, 2004]. In agreement, a recent study in a different Mediterranean forest in Israel reported that root exudation rates were highest in the dry season and were associated with high soil temperature and low soil moisture [Jakoby et al, 2020]. Indeed, the inverse relationship between ARQ ts vs. ARQ sa at cm in the deciduous Q.…”
Section: Tree Stems Arqmentioning
confidence: 83%
“…Trees invest a substantial part of their photosynthesized carbon into root exudates that entice and presumably feed plant-beneficial and root-associated microbiota (Bais et al, 2006; Badri and Vivanco 2009; Karst et al, 2017; Jakoby et al, 2020). In parallel, the rhizosphere microbes can promote plant growth through various mechanisms such as increasing the availability of nutrients, secreting phytohormones, suppressing pathogens, or having positive effects on the plant metabolism (Perez-Montano et al, 2014; Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that roots of both conifer and broadleaf tree species in an evergreen Mediterranean forest increase their exudation flux during the long dry season (Jakoby et al, 2020). This occurred in spite of the sharp decrease of tree carbon uptake along the dry season, and more so in the coniferous Cupressus sempervirens .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation